A Feasibility study on Tropical Fresh TM Banana Spread - Arigo, Agnes R. (College of Engineering, 1998)
Banana is a nutritious food known world-wide. Under normal economic conditions, supply of bananas may not be suitable for shipment as fresh fruit, due to either or both of the following reasons: (1) they do not meet the standard specifications for the export trade; and/or (2) they are not of the desired variety. An oversupply of the fruit in one particular area may also be attributed to its lack of transport facilities. A partial solution to this situation is a processes product like a fruit spr4ead. It is for this reason that the group decided to look into the feasibility of producing and selling banana spreads. Tropical Fresh, as the product is to be known, is produced as a fruit-based sandwich spread. The ripe, sound variety of the banana with strong characteristic aroma and flavor, specifically, lakatan, is used to make the spread. With the increasing demand for convenience and health foods, Tropical Fresh can very well fit in. Apart from being used as spread for bread, pancakes and waffles, it can also serve as cake fillings or icings, with ice cream, cereal, and as condiment. At the same time, carrying the right nutrients found in a banana, it is the most appropriate substitute for junk foods. Tropical Fresh besides being low in fat, also has the advantage of being low in price, lower than the leading competitor brand. A market study on the product identified the target market to be primarily households in Metro Manila, with family members at least 5 years old, and who are willing and can afford to buy Tropical Fresh. With the demand remarkably exceeding supply, the group established a yearly production volume equal to 9.93% of the total supply of sandwich spreads in Metro Manila. The lower price of the product which is Php 35.60 per 320-gram bottle, and aggressive marketing in the form of free product sampling, coupled with radio, billboard, and newspaper advertisements, make it feasible for Tropical Fresh Banana Spread to penetrate the industry. The total marketing budget for the introduction of Tropical Fresh is Php 1,772,670.40. The technical analysis of the project showed that the company can meet demand for the product by adopting an exact production with varying workforce level plan in the five year planning horizon, except in year 2000 wherein a constant workforce level with varying overtime plan is called for. The number of workforce corresponds to the capacity specifications that can produce the desired output level. The number of loadings is fixed at 21 per day. The production of Tropical Fresh requires 10 food processing equipment, 2 storage areas for raw materials and finished products, and 876 square meters of land. The manpower requirement on the first year is 80 workers per month which will mostly come from the neighboring areas. All these production requirements can be accommodated by the plant located at Kalabaw Rd., Bagong Hagonoy, Taguig having an area of 1,000 square meters. The total project cost for the first year is computed to Php 96,192,103.49. Only 75% of the total capital required (equivalent to nine months' worth) will be raised. Using only the fixed assets as collateral, the equity to loan ration is computed to be 9:1. The amount to be shouldered by the stockholders is Php 67,334,472.44 and the remaining Php 6,982,933.68 will be loaned from Metrobank at an annual interest rate of 18.25%. payable in two years. In the organization management study, the form of organization established to pursue the project is that of a corporation. It shall be composed of the President (CEO), four managers, and other staff. A total of twenty-seven salaried personnel will be employed. The results of financial analysis suggests that the project is financially feasible and attractive. In fact, income for the first year is Php 77,029,709.28. The project is profitable as shown by the financial ratios which also revealed that the company is both liquid and solvent early into the first five years of its operations. The computed internal rate of return (IRR) for the project is 105% with a payback period of approximately 1 year and 1 month. A listing of costs and benefits in undertaking the project was provided in the social profitability analysis. Far-reaching benefits to both the community in the chosen site and the local and national governments are identified. These include additional employment opportunities, payment of municipal and corporate taxes by the corporation, payment of withholding tax by the personnel, increase in utilization of local materials, and growth of local manufacturers and traders of equipment. IT can, therefore, be concluded that Tropical Fresh Banana Spread has sufficient market, and is technically feasible, financially attractive, and socially profitable to all entities affected.